Virulence distribution and frequency of Puccinia striiformis f. sp. hordei, causing stripe rust of barley in northern parts of India - O.P. GANGWAR*; S.K. JAIN, M. PRASHAR, S.C. BHARDWAJ, (Indian Phytopathology, 2014)
Three hundred seven yellow rust samples/isolates, primarily from North Indian states during 2004-05 to 2010-11, were collected during field survey in the main crop season of barley. They were subjected to pathotype identification based on three sets of differentials. Five pathotypes were identified from 307 isolates. New virulence was not identified in any of the sample. Pathotype 1S0 (M) was the most frequent and identified in 199 isolates (64.82%). Pathotype 0S0-1 (24) consisted of 54 isolates. Gene Yr1 virulent pathotype 1S0 which was first identified from Shimla in 1987 was widely distributed across the North Indian states. All the identified pathotypes were avirulent on Yr2, Yr3, Yr4, Yr5, Yr7, Yr8, Yr9+ and Yr10 genes. Weighted average frequency and frequencies dynamics was higher for the pathotype 1S0. Frequencies of pathotypes 1S0 and 0S0-1 varied from 55.22% to 85.29% and 0% to 38.81%, respectively. Shannon’s relative index (HSR) indicated low diversity in Puccinia striiformis f. sp. hordei (Psh) population in northern parts of India.